The Broad Concept of “Spasticity-Plus Syndrome” in Multiple Sclerosis: A Possible New Concept in the Management of Multiple Sclerosis Symptoms - Fernández, Óscar; Costa-Frossard, Lucienne; Martínez-Ginés, Marisa; Montero, Paloma; Prieto, José Maria; Ramió, Lluis (Frontiers in Neurology, 2020)
MS pathology progressively affects multiple CNS areas. Due to this fact, MS produces a wide array of symptoms. Symptomatic therapy of one MS symptom can cause or worsen other unwanted symptoms (anticholinergics used for bladder dysfunction produce impairment of cognition, many MS drugs produce erectile dysfunction, etc.). Appropriate symptomatic therapy is an unmet need. Several important functions/symptoms (muscle tone, sleep, bladder, pain) are mediated, in great part, in the brainstem. Cannabinoid receptors are distributed throughout the CNS irregularly: There is an accumulation of CB1 and CB2 receptors in the brainstem. Nabiximols (a combination of THC and CBD oromucosal spray) interact with both CB1 and CB2 receptors. In several clinical trials with Nabiximols for MS spasticity, the investigators report improvement not only in spasticity itself, but also in several functions/symptoms mentioned before (gait, spasms, cramps, sleep, bladder function, pain and tremor). We can conceptualize and therefore, hypothesize, through this indirect information, that it could be considered the existence of a broad “Spasticity-Plus Syndrome” which involves, apart from spasticity itself, the rest of the mentioned functions/symptoms, probably because they are interlinked after the increase of muscle tone and mediated, at least in part, in the same or close areas of the brainstem. If this holds true, there exits the possibility to treat several spasticity related symptoms induced by MS pathology with a single therapy, which would permit to avoid the unnecessary adverse events effects produced by polytherapy. This would result in an important advance in the symptomatic management of MS.